2019
DOI: 10.1021/acsmedchemlett.9b00388
|View full text |Cite
|
Sign up to set email alerts
|

An Alkyne-functionalized Arginine for Solid-Phase Synthesis Enabling “Bioorthogonal” Peptide Conjugation

Abstract: Lately, amino-functionalized N ω-carbamoylated arginines were introduced as arginine surrogates enabling peptide labeling. However, this approach is hardly compatible with peptides also containing lysine or cysteine. Here, we present the synthesis of an alkyne-functionalized, N ω-carbamoylated arginine building block (7), which is compatible with Fmoc-strategy solid-phase peptide synthesis. The alkynylated arginine was incorporated into three biologically active linear hexapeptides and into a cyclic pentapepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 20 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…Figure 1B), the antagonistic potencies of 18, 20, 23 and 28 (Table 2) were considerably lower compared to binding data (pK i values) obtained from radioligand competition binding studies (Table 1). Increasing the incubation times in the M 2 R IP1 assay from 30 min to 180 min (preincubation of the cells with antagonist) and from 60 min to 90 min (continued incubation after addition of the agonist CCh), as well as lowering the temperature from 37 °C to 22 °C during preincubation, did not affect (18,28) or led to a moderate increase (20,23) in pIC 50 values (Table 2). Possibly, the type of interaction between 18, 20, 23 or 28 and CCh is different from how the small antagonist 31 inhibits the CCh induced IP1 accumulation, which is supported by a much better correlation of the pIC 50 (pK b ) and pK i value in case of 31 (pIC 50 : 8.09 (Table 2), corresponding pK b : 8.66, pK i : 9.04 (Table 6)).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Figure 1B), the antagonistic potencies of 18, 20, 23 and 28 (Table 2) were considerably lower compared to binding data (pK i values) obtained from radioligand competition binding studies (Table 1). Increasing the incubation times in the M 2 R IP1 assay from 30 min to 180 min (preincubation of the cells with antagonist) and from 60 min to 90 min (continued incubation after addition of the agonist CCh), as well as lowering the temperature from 37 °C to 22 °C during preincubation, did not affect (18,28) or led to a moderate increase (20,23) in pIC 50 values (Table 2). Possibly, the type of interaction between 18, 20, 23 or 28 and CCh is different from how the small antagonist 31 inhibits the CCh induced IP1 accumulation, which is supported by a much better correlation of the pIC 50 (pK b ) and pK i value in case of 31 (pIC 50 : 8.09 (Table 2), corresponding pK b : 8.66, pK i : 9.04 (Table 6)).…”
Section: Resultsmentioning
confidence: 98%
“…For this reason, the pharmacophore (ligand) and the fluorophore are often held apart by a linker or spacer moiety. [6][7][8] There are numerous reports on fluorescent probes for GPCRs, for instance for neuropeptide Y, [9][10][11][12][13][14] histamine, [15][16][17][18][19] opioid, [20][21][22] dopamine, 23,24 neurotensin, [25][26][27][28] and adenosine 29 receptors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This had not been achieved before with small peptides such as hexapeptides. The study demonstrates that the guanidine/carbamoylguanidine bioisosteric approach, reported to be useful for peptide labeling via arginine residues, 19,24,38,39 can be successfully exploited for the preparation of cyclic peptidic receptor ligands with high affinity. The cyclic peptides 18 (UR-AK86c) and 24 (UR-AK95c) were shown to be substrates of angiotensin-converting enzyme (EC 3.4.15.1), which cleaves 18 and 24 at the Leu 4 − Arg 5 bond in their C-terminal exocyclic tripeptide sequence, resulting in moderate in vitro plasma stabilities of 18 and 24 (t 1/2 ca.…”
Section: ■ Conclusionmentioning
confidence: 95%